P034 EXERCISE AS ADJUNCTIVE THERAPY IN INFLAMMATORY BOWEL DISEASE: AN EDUCATIONAL INTERVENTION CAN INCREASE PHYSICIAN AWARENESS. (18th January 2018) - Fairfield, Bradley; Rowe, Anthony; Borum, Marie L
Abstract: Exercise has been shown to be safe and have symptom reduction in patients with inflammatory bowel disease (IBD). However, there has been inconsistent incorporation of physical activity in IBD management. This study evaluated physician awareness of exercise upon IBD and evaluated the impact of an educational intervention upon integrating exercise into IBD treatment plans. Surveys were administered to physicians in a university gastroenterology practice which addressed the frequency of inquiring about and recommending exercise to IBD patients. A week following survey administration, a brief educational presentation of the current data on the effect of exercise upon IBD was given. Physicians were subsequently surveyed about whether the presentation and the likelihood that exercise would be recommended to IBD patients. Likert scales were used to evaluate ordinal data. All surveys were anonymous. 9 of 14 physicians (64.3%) completing the initial survey indicated that most IBD patients were rarely asked about their physical activity (0 always, 0 usually, 2 sometimes, 6 rarely, 1 never) and that most patients rarely or never received recommendations for exercise (0 always, 2 usually, 1 sometimes, 4 rarely, 2 never). Following the educational presentation, 9 of 14 physicians (64.3%) responded that the information was helpful (5 strongly agreed, 4 agreed) and that increased effort would be made to discuss exercise (5 strongly agreed, 4 agreed). No respondents were neutral, disagreed or strongly disagreed with the information or recommending exercise. This study demonstrated that physicians inconsistently ask or recommend exercise to IBD patients and that an educational intervention can increase physician awareness of the therapeutic effects of exercise upon IBD. While this study is limited based upon sample size and self-reporting, it can serve as a basis for additional investigations that focus on exercise, IBD and optimization of clinical outcomes.